The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/tii.2021.3093300
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Farm Power Tracking Via Preview-Based Robust Reinforcement Learning

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…There are also several essential differences between the work in this paper and Ref. [4]. Firstly, these two studies consider different tasks.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…There are also several essential differences between the work in this paper and Ref. [4]. Firstly, these two studies consider different tasks.…”
Section: Introductionmentioning
confidence: 84%
“…Though single turbine's control strategies have been widely studied, directly employing these methods to control every turbine in a wind farm via a non-cooperative way can lead to significantly degraded operating efficiency. A lot of studies [2], [3], [4] have demonstrated that the greedy strategy (i.e. every turbine in the farm aims to maximize its own power outputs) is not the optimal control strategy for farm-level power generation maximization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Deep Reinforcement Learning (DRL) has achieved great success in solving computationally challenging decision-making problems, such as Atari [16], Go [17], and StarCraft [18]. Due to its powerful model-free optimisation capabilities, DRL has recently been used for real-time control problems in wind farms, such as output power maximisation [19], [20] and power tracking [21]. However, these works do not take into account the fast frequency response of the wind farm, and they do not model the power grid or the mechanical structure of WTs.…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted worldwide research interest and been applied to many important fields [15], [16], [17]. Notably, several recent studies [18], [19], [20], [21] successfully applied DRL to address wind farm control tasks. They verified the feasibility of employing DRL to maximize wind farms' economic profitability.…”
Section: Introductionmentioning
confidence: 99%